Peptidylarginine deiminase 2 citrullinates MZB1 and promotes the secretion of IgM and IgA - Geary, Benjamin; Sun, Bo; Tilvawala, Ronak R.; Barasa, Leonard; Tsoyi, Konstantin; Rosas, Ivan O.; Thompson, Paul R.; Ho, I-Cheng (Frontiers in Immunology, 2023)
Introduction MZB1 is an endoplasmic reticulum residential protein preferentially expressed in plasma cells, marginal zone and B1 B cells. Recent studies on murine B cells show that it interacts with the tail piece of IgM and IgA heavy chain and promotes the secretion of these two classes of immunoglobulin. However, its role in primary human B cells has yet to be determined and how its function is regulated is still unknown. The conversion of peptidylarginine to peptidylcitrulline, also known as citrullination, by peptidylarginine deiminases (PADs) can critically influence the function of proteins in immune cells, such as neutrophils and T cells; however, the role of PADs in B cells remains to be elucidated. Method An unbiased analysis of human lung citrullinome was conducted to identify citrullinated proteins that are enriched in several chronic lung diseases, including rheumatoid arthritis-associated interstitial lung disease (RA-ILD), chronic obstructive pulmonary disease, and idiopathic pulmonary fibrosis, compared to healthy controls. Mass spectrometry, site-specific mutagenesis, and western blotting were used to confirm the citrullination of candidate proteins. Their citrullination was suppressed by pharmacological inhibition or genetic ablation of PAD2 and the impact of their citrullination on the function and differentiation of human B cells was examined with enzyme-linked immunosorbent assay, flow cytometry, and co-immunoprecipitation. Results Citrullinated MZB1 was preferentially enriched in RA-ILD but not in other chronic lung diseases. MZB1 was a substrate of PAD2 and was citrullinated during the differentiation of human plasmablasts. Ablation or pharmacological inhibition of PAD2 in primary human B cells attenuated the secretion of IgM and IgA but not IgG or the differentiation of IgM or IgA-expressing plasmablasts, recapitulating the effect of ablating MZB1. Furthermore, the physical interaction between endogenous MZB1 and IgM/IgA was attenuated by pharmacological inhibition of PAD2. Discussion Our data confirm the function of MZB1 in primary human plasmablasts and suggest that PAD2 promotes IgM/IgA secretion by citrullinating MZB1, thereby contributing to the pathogenesis of rheumatoid arthritis and RA-ILD.